Sensitivity of Pine Island Glacier to observed ocean forcing. Issue 20 (30th October 2016) - Christianson, Knut; Bushuk, Mitchell; Dutrieux, Pierre; Parizek, Byron R.; Joughin, Ian R.; Alley, Richard B.; Shean, David E.; Abrahamsen, E. Povl; Anandakrishnan, Sridhar; Heywood, Karen J.; Kim, Tae‐Wan; Lee, Sang Hoon; et al.
Abstract: We present subannual observations (2009–2014) of a major West Antarctic glacier (Pine Island Glacier) and the neighboring ocean. Ongoing glacier retreat and accelerated ice flow were likely triggered a few decades ago by increased ocean‐induced thinning, which may have initiated marine ice sheet instability. Following a subsequent 60% drop in ocean heat content from early 2012 to late 2013, ice flow slowed, but by < 4%, with flow recovering as the ocean warmed to prior temperatures. During this cold‐ocean period, the evolving glacier‐bed/ice shelf system was also in a geometry favorable to stabilization. However, despite a minor, temporary decrease in ice discharge, the basin‐wide thinning signal did not change. Thus, as predicted by theory, once marine ice sheet instability is underway, a single transient high‐amplitude ocean cooling has only a relatively minor effect on ice flow. The long‐term effects of ocean temperature variability on ice flow, however, are not yet known. Key Points: Pine Island Glacier speed is correlated with ocean temperature Grounded ice speed slowed by only 1% despite 60% drop in ocean heat content Ice speed recovered after the cold‐ocean anomaly ended